Effect of -NBOMe Compounds on Sensorimotor, Motor, and Prepulse Inhibition Responses in Mice in Comparison With the 2C Analogs and Lysergic Acid Diethylamide: From Preclinical Evidence to Forensic Implication in Driving Under the Influence of Drugs - Tirri, Micaela; Bilel, Sabrine; Arfè, Raffaella; Corli, Giorgia; Marchetti, Beatrice; Bernardi, Tatiana; Boccuto, Federica; Serpelloni, Giovanni; Botrè, Francesco; De-Giorgio, Fabio; Golembiowska, Krystyna; Marti, Matteo (Frontiers in Psychiatry, 2022)
In the last decade, the market for new psychoactive substances has been enriched by numerous psychedelic phenethylamines, which mimic the psychoactive effect of lysergic acid diethylamide (LSD). In particular, the -NBOMe series, which are more potent than their 2C compounds analogues, are considered worthy substitutes for LSD by users. The purpose of this study was to assess the effects of 25H-NBOMe and its halogenated derivatives (25I-NBOMe and 25B-NBOMe) in comparison to their 2C compounds analogues and LSD on the sensorimotor (visual, acoustic, and overall tactile), reaction time, spontaneous (total distance travelled) and stimulated (drag, accelerod test) motor activity, grip strength test, and prepulse inhibition (PPI) responses in mice. Systemic administration of -NBOMe, 2C compounds analogues, and LSD (0.001–10 mg/kg) differently impaired the sensorimotor, reaction time, motor, and PPI responses in mice. In particular, halogenated (25I and 25B)-NBOMe derivatives appear to be more effective than the entire class of 2C compounds analogues in altering visual and acoustic responses, affecting reaction time, and motor and sensory gating in PPI test. In fact, the specific rank order of compounds potency for nearly all of the experiments showed that (25I and 25B)-NBOMe were more potent than 2C compounds analogues and LSD. -NBOMe and 2C compounds analogues impaired not only the reception of incoming sensory stimuli (visual and acoustic), but their correct brain processing (PPI) in an equal and sometimes stronger way than LSD. This sensory impairment directly affected the spontaneous motor response and reaction time of mice, with no change in performance in stimulated motor activity tests. These aspects should be carefully considered to better understand the potential danger that psychedelic phenethylamines, in particular -NBOMe, may pose to public health, with particular reference to decreased performance in driving and hazardous works that require special sensorimotor skills